Sport and physical education in Germany - Naul, Roland; Hardman, Ken, 1938- (International Society for Comparative Physical Education and Sport series., 2002)
Sport and physical education represent important components of German national life, from school and community participation, to elite, international level sport. This unique and comprehensive collection brings together material from leading German scholars to examine the role of sport and PE in Germany from a range of historical and contemporary perspectives. Key topics include:* sport and PE in pre-war, post war and re-unified Germany* sport and PE in schools* coach education* elite sport and sport science* women and sport* sport and recreation facilities. This book offers an illuminating insi.